FUTURE PROSPECTS AND STRATEGIC DEVELOPMENT OF TRANSPORT CORRIDORS IN CENTRAL ASIA (World Economics and Finance Bulletin, 2024)
The development of transport corridors in Central Asia represents a crucial driver of economic growth, regional connectivity, and sustainable development. Positioned at the crossroads of Europe and Asia, Central Asia has the potential to become a pivotal transit and trade hub by enhancing its transport infrastructure and establishing effective corridors. This article explores the future prospects and strategic initiatives for transport corridor development in Central Asia, examining the role of international partnerships, infrastructure investments, and technological advancements in shaping this sector. Through an analysis of current challenges and opportunities, this study offers insights into the potential impact of improved transport corridors on regional integration, trade expansion, and socio-economic development.